Migrant workers, consruction industry and covid-19: Insights from mohali and panchkula - Vishnu (IISER Mohali, 2022)
The inter-state labour migration plays an important role in the social and economic development in both origin and destination places. COVID-19 led pandemic has adversely impacted on various sectors in the economy and construction sector is one of the worst affected industries. We witnessed that migrant workers are worst hit by the pandemic. Thus, this study intends to understand the plight of migrant workers in the construction industry during COVID-19 in two northern cities, namely, Mohali (Punjab) and Panchkula (Haryana). It was found that workers mostly come from from states like UP, Bihar, Jharkhand, and Chattisgarh where there is lack of employment opportunities and also have scarce resources. Workers assume that migration may lead to raise their level of income and standard of living, However, the problems faced by them at the destination place are plenty and much higher than those of native workers. Living and working conditions of the workers are also not up to the mark as per their expectation. The challenges related to inter-state migration are complex. Male members are the main workers in the industry whereas female workers are predominantly employed as casual workers. It was also found that none of the construction workers receive any safety equipments across work sites in both the cities. Further, about one fourth (25%) of the workers don’t receive minimum wages. The various labour laws applicable to migrant workers fail to protect the rights of the migrant workers due to flaws and lack of effective implementation of these laws which leads to the exploitation of the migrant workers. The migrant workers are exploited by the persons involved in the process of their employment such as contractors. The lack of awareness about the various labour laws among the migrant workers also leads to the exploitation of them. The migrant workers also don’t have awareness about the government policies and schemes applicable to them which avoids the
Keywords: Migrant workers; covid-19; consruction; Industry